Skip to content

Latest commit

 

History

History
149 lines (83 loc) · 3.64 KB

File metadata and controls

149 lines (83 loc) · 3.64 KB

Errata of Modelling Computing Systems (Moller & Struth)

Chapter 1

Solution 1.16 (page 410)

In the second part of the solution, to part 1) the text reads:

'This can be expressed more succinctly as p = ...'

Where it should read:

'This can be expressed more succinctly as q = ...'

Solution 1.12.3 (p. 408)

There are two mistakes:

  • the root of the tree should be ∧ instead of ∨
  • the right sub-tree should be P instead of Q

Solution 1.21 (p. 412)

The last word of the solution should not read 'induction' but rather 'implication'.

Solution 1.26 (p. 414)

"However, the formulae p and q are equivalent, ...", this should be "However, the formulae p and r are equivalent, ..."

Solution 1.27.1 (p. 415)

There are two mistakes:

  • When the Commutativity rule is applied, ∨ is accidentally changed to ∧
  • The last rule should be the Contradiction law instead of Tautology

It should be:

...
<=> (p ∧ q) ∨ false  (Commutativity)
<=> p ∧ q            (Contradiction)

Solution 1.27.6 (p 415)

In the second to last step (labelled Distributivity) the formula should read:

(¬p ∨ r) ∧ (¬q ∨ r)

Chapter 2

Example 2.17 (p.71)

The first sentence states that Amanda invites six friends to her birthday party. This should be five friends.

Solution 2.28 (p. 420)

The Commutative step mistakenly introduces ∩ which should be ∪. The last two steps should be

  ...
  = (A ∩ B) ∪ ∅  (Commutativity law)
  = A ∩ B        (Empty set law)

Exercise 2.30.2

The subformula $P \Leftrightarrow Q$ should have parentheses around it, so the complete formula should be:

$(P \Leftrightarrow Q) ~ \Leftrightarrow ~ (P \Rightarrow Q) \wedge (Q \Rightarrow P)$

Chapter 3

Example 3.14 (p.98)

The third bullet states

x = bc

Which should be

z = bc

Chapter 4

Section 4.3 - page 123

Under heading 4, the formula $P(x) \wedge Q(x)$ should be $P(x) \vee Q(x)$.

Solution 4.7.2

Remember that $\forall$ and $\exists$ bind stronger than other logical connectives when there are no parentheses. So the given solution actually has a free variable, written here in bold:

$\forall x ~ (\exists y ~ Mother(x, y) \Rightarrow Parent(x, \textbf{y}) \wedge Female(x))$

Instead, one correct solution is:

$\forall x ~ (\exists y ~ Mother(x, y) \Rightarrow \mathbf{\exists y} Parent(x, y) \wedge Female(x))$

Note that the following formula is not a good answer to the question:

$\forall x ~ (\exists y ~ (Mother(x, y) \Rightarrow Parent(x, y) \wedge Female(x)))$

Why? It states that for every person $x$, there exists a person $y$, such that the implication is true. That is true: for any person $x$, you can choose $y$ to be that same person, and the implication will hold (a person can never be their own mother). However, the sentence does not really express the intended property about mothers anymore.

Chapter 5

Example 5.17

The proof starts with "Assume $A \cap B = B$". This should read "Assume $A \cap B = A$".

Chapter 6

Exercise 6.15

The exercise should be:

Prove that $A \cong B$ for any countably infinite sets A and B.

Chapter 7

Example 7.8

The definition of grandfather should be:

$Grandfather = Father \circ Parent $

Exercise 7.9

The solutions again confuse the order of composition in the definition of Nephew and Uncle.

Definition 7.11 (p. 191)

"anytisymmetric" is a typo, it should of course be "antisymmetric"

Chapter 8

Solution 8.10 (p.443)

The general solution is

$f_n = f_{n-1} + f_{n-2}$

Chapter 9

Solution for 9.12

The solution states:

"if (a, b) = (fn, fn+1) then (fn+1, fn+2) = (a+b, b)"

This should be (b, a+b).